2014 IEEE International Power Modulator and High Voltage Conference (IPMHVC) 2014
DOI: 10.1109/ipmhvc.2014.7287213
|View full text |Cite
|
Sign up to set email alerts
|

Optimal power system and grid interface design considerations for the CLICs klystron modulators

Abstract: The Compact Linear Collider (CLIC) is an electron-positron collider under study at CERN with the aim to explore the next generation of high precision/high energy particles physics. The CLIC's drive beams will be accelerated by approximately 1300 klystrons, requiring highly efficient and controllable solid state capacitor discharge modulators. Capacitor charger specifications include the requirement to mask the pulsed effect of the load from the utility grid, ensure maximum power quality, control the derived DC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…in the case of bus bar failure the power system cannot be reconfigured to deliver power to all klystron modulators. In [5] the solution with parallel bus bars, providing higher availability of the accelerator, with an increase of cost, is introduced. The availability of the power system is estimated using fault tree analysis [11] and it has been shown that all considered solutions with single bus bar structure have similar unavailability of about 170 min/year while structures with parallel bus bars have unavailability of about 30 min/year.…”
Section: Power System Designmentioning
confidence: 99%
See 2 more Smart Citations
“…in the case of bus bar failure the power system cannot be reconfigured to deliver power to all klystron modulators. In [5] the solution with parallel bus bars, providing higher availability of the accelerator, with an increase of cost, is introduced. The availability of the power system is estimated using fault tree analysis [11] and it has been shown that all considered solutions with single bus bar structure have similar unavailability of about 170 min/year while structures with parallel bus bars have unavailability of about 30 min/year.…”
Section: Power System Designmentioning
confidence: 99%
“…Based on the results from [5], the number of MV bus bars is fixed at 6, while the number of LMV bus bars is 6 in the case of 12 kV switchgear and 12 in the case of 7.2 kV switchgear. In the case of lower LMV voltages the fault currents at these bus bars are beyond the breaking capabilities of standard devices.…”
Section: Power System Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Each phase has two arms, comprised of the series connection of an arm inductor and a defined number of half bridge submodules (forming a chainlink). In this paper the MMC is the grid interface for a number of klystron modulators [3], [4] used in the next generation linear accelerator under feasibility studies at CERN [5].…”
Section: Introductionmentioning
confidence: 99%
“…The third section analyses the pulsed load effects on the average arm powers and suggests an analytical solution for the circulating current reference to achieve balancing. The fourth section presents the simulation results and their comparison with the analytically derived expectations on a 400 kV AC/20 kV DC/16.6 MW converter (full scale rating [3]). The fifth section presents the experimental results from a laboratory scale prototype rated at 7 kW, for 225 V AC voltage and 400 V DC voltage.…”
Section: Introductionmentioning
confidence: 99%